Precise control of variable-height laser metal deposition using a height memory strategy. (September 2020) - Shi, Tuo; Shi, Jianjun; Xia, Zhixin; Lu, Bingheng; Shi, Shihong; Fu, Geyan
Highlights: An IBPF cladding nozzle was applied for deposition of the overhanging structures. A deposition height sensor and a closed-loop control system were developed. The uneven top surface produced during the variable height deposition process can be memorized and smoothed by the PI controller. Segmented deposition heights control strategy was proposed for the deposition of unequal-height parts. Abstract: In respect of laser metal deposition (LMD) 3-D additive manufacturing technology, the method of non-parallel slicing is applied for the deposition of the overhanging and unequal-height parts and is capable of improving the deposition accuracy, stability and efficiency. Nevertheless, the produced uneven top surface derived from variable height deposition process has a possibility to result in instability and even failure of the deposition. In this study, the novel control strategies for the precise control of the unequal-height part were proposed. An inside-beam powder feeding nozzle was applied for the deposition with large overhanging angle. Based on a developed deposition height control system, multiple PI controllers were designed for varying desired deposition heights in an unequal-height layer. The actual heights of the uneven top surface in different positions were memorized by the deposition of a layer, and the process parameters for the next layer could be planned in advance to smooth this unevenness. Under the proposed control strategies, a geometrical stable and convergent process was made achievable when depositing a "fan-shaped" part and a "bent-pipe-shaped" part as the typical overhanging and unequal-height structures. The microstructures were observed to be uniform and compact, and the grain sizes and microhardness in different height positions were found to vary slightly.